2018
DOI: 10.1037/stl0000116
|View full text |Cite
|
Sign up to set email alerts
|

Counseling psychology students’ perceptions of faculty multicultural competence.

Abstract: One current focus of training in applied psychology programs is multicultural competence. Research on multicultural competence has focused on students and on clinical supervisors. However, much training in multicultural competence occurs in classrooms and within training programs, and there has been limited examination of the multicultural competence of faculty. Using consensual qualitative research (CQR) methodology, we examined counseling psychology doctoral student perceptions of the multicultural competenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In addition, this training can enhance the faculty's capacity to support students from diverse backgrounds. Faculty's increased multicultural competence will help programs be more intentional in their efforts to recruit and retain REM students (Koch et al, 2018; Proctor & Truscott, 2012). The lack of racial and ethnic diversity in the profession has been a longstanding issue; graduate programs play an important role in making the profession more diverse.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this training can enhance the faculty's capacity to support students from diverse backgrounds. Faculty's increased multicultural competence will help programs be more intentional in their efforts to recruit and retain REM students (Koch et al, 2018; Proctor & Truscott, 2012). The lack of racial and ethnic diversity in the profession has been a longstanding issue; graduate programs play an important role in making the profession more diverse.…”
Section: Discussionmentioning
confidence: 99%
“…Without proper grounding in the historical context of BIPOC students, trainers risk pathologizing student behavior (as seen in examples described in Shin, 2015). Supervisory relationships can inhibit supervisee growth with supervisors who are viewed as culturally insensitive (Koch et al, 2018). This happens when our readiness for change is based on performative change, or cursory understanding of culture without a true reconciliation process including a historical and developmental framework.…”
Section: Whiteness and White Supremacymentioning
confidence: 99%
“…More specifically, the relationship between instructor competence and trainee competence, particularly the impact of instructor multicultural competence on training, has been explored with limited research. One study examined how doctoral students in counseling psychology defined and perceived the multicultural competence of faculty (Koch et al, 2018). This qualitative study found six domains of students' perceptions of faculty multicultural competence, including faculty expertise, faculty-student relationships, faculty initiative, perceptions of faculty as agents of social change, faculty attributes, and faculty limitations (Koch et al, 2018).…”
Section: Multicultural Competencementioning
confidence: 99%
“…One study examined how doctoral students in counseling psychology defined and perceived the multicultural competence of faculty (Koch et al, 2018). This qualitative study found six domains of students’ perceptions of faculty multicultural competence, including faculty expertise, faculty-student relationships, faculty initiative, perceptions of faculty as agents of social change, faculty attributes, and faculty limitations (Koch et al, 2018). These six domains reflect how students utilize their perceptions of faculty members and their own relationships with them, both of which extend beyond the classroom, as means to assess faculty multicultural competence.…”
Section: Multicultural Competencementioning
confidence: 99%
See 1 more Smart Citation